Epigenetic therapy for the treatment of epithelial ovarian cancer: A clinical review - Haller J. Smith; J. Michael Straughn; Donald J. Buchsbaum; Rebecca C. Arend (Elsevier, 2017)
Despite a good initial response to chemotherapy, the majority of patients with epithelial ovarian cancer will eventually recur and die of their disease. The introduction of targeted therapies to traditional chemotherapy regimens has done little to improve overall survival in women with ovarian cancer. It has become increasingly apparent that the cancer epigenome contributes significantly to the pathogenesis of ovarian cancer and may play an important role in cell proliferation, metastasis, chemoresistance, and immune tolerance. Epigenetic therapies such as DNA methyltransferase inhibitors and histone deacetylase inhibitors have the potential to reverse these epigenetic changes; however, more research is needed to determine how to incorporate these agents into clinical practice. In this review, we discuss the common epigenetic changes that occur in epithelial ovarian cancer, the current epigenetic therapies that may target these changes, and the clinical experience with epigenetic therapy for the treatment of epithelial ovarian cancer.